Tingkat Pengetahuan Gizi dan Status Gizi Siswa SMP - Desiana Merawati (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
This research investigated nutrition knowledge level and nutrition status of junior secondary school students in Malang city. Subjects of the research were 253 male students and 248 female students. The research found that nutrition knowledge level and nutrition statues of junior secondary school students in Malang city were not in the good criteria.